Pengaruh Variasi Persentase Campuran Polymer Polyester dan Vinyl Ester Terhadap Kekuatan Tegangan Lentur - Nusyirwan Adnand; R Mutya; Firman Ridwan; Hairul Abral; Hendery Dahlan; Eka Satria (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
Polymer mixture of polyester and vinyl ester is widely used in engineering fields such as for car bumpers, boat bodies, ultra-light aircraft wings, wind turbine blades and others. One of the requirements to meet the application aspects in the engineering field is the ability of the material to withstand bending loads. For this reason, it is necessary to test the flexural stress characteristics of the mixture of the two polymers of unsaturated polyester and unsaturated vinyl ester. The aim is to find out which of the two polymer blends obtains superior flexural resistance properties from each of the polymers with respect to the blend percentage. To determine the flexural stress value of the polyester and vinyl ester mixture, a flexural stress test was carried out with reference to the standard flexural test or the bending test used based on ASTM D 790 by varying the composition of the mixture 100%: 0%, 90%: 10%, 80%: 20%, 60%:40%, and 0%:100%. From the results of the bending stress test on specimens with variations in the composition of polyester and vinyl ester with the hand lay-up method, the highest bending stress value is found in the composition of 60% polyester and 40% vinyl ester, which is 126.88 MPa ( an increase in maximum flexural strength of 255%)